Prospek Budidaya Kedelai Berdasarkan Kebutuhan Air Tanaman dan Zona Agroklimat di Provinsi Jambi - Najla Anwar Fuadi; M. Yanuar Jarwadi Purwanto; Afri Fajar (Jurnal Irigasi, 2020)
Soybean (Glicine max) has the potential to be developed because it cannot only be processed into foodstuffs but also become livestock feed. In addition to using technology, enhancement of crop production can be done by looking at water availability and pay attention to the weather factors, especially to increase crop intensity. This research aims to determine the crop water requirements based on the agroclimatic zone. The quantitative descriptive analysis and data processing were conducted using the Cropwat model. This model was created by FAO specialists to provides an opportunity for automation of all the necessary calculations for evapotranspiration determination. Cropwat is an easy-to-operate software that can minimize human error. Climate classification was identified based on precipitation data in Jambi province respectively in Muaro Jambi Regency at Sultan Thaha Station, Jambi Palmerah, and Depati Parbu. The agroclimatic zone for those areas, respectively, are D1, D2, and E2. Based on the rainfall, all three districts are feasible for soybean cultivation with average rainfall between 127.11 mm – 192.51 mm per month. The amount of crop water requirements is also an essential factor for cultivating a plant so that the water can be administered according to the needs of plants and can provide optimal production. Based on water balance, the surplus in Muaro Jambi Regency Jambi Province occurs in January, February, March, April, September, October and December. East Tanjung Jabung Regency surplus is in January, February, March and April. West Tanjung Jabung Regency surplus occurs in January, February, March, October, November and December. The results of this calculation indicate that Jambi Province has the potential to cultivate soybean plants because they have sufficient water availability.